ANALISIS KAUSALITAS RUNTUHNYA KERAJAAN SINGASARI AKIBAT DARI GEOPOLITIK GLOBAL SERTA TRANSFORMASI POLITIK MENUJU BERDIRINYA KERAJAAN MAJAPAHIT - Irsyad Arjuna Valentino Mesy Syah Putra Valentine; Andini Ramadhani; Fatimatuz Zahro; Nafisa Desi Wulandari; Agus Mursidi (Keraton: Journal of History Education and Culture, 2026)
The Singasari Kingdom was a dominant political entity in the 13th-century Indonesian archipelago that suffered a sudden collapse in 1292. This study aims to analyze the causality of Singasari's fall and the process of political transformation leading to the establishment of the Majapahit Kingdom. Utilizing a literature review method and a critical historical approach, this research explores the interaction between internal dynamics in the form of political fragmentation and global intervention by the Mongol Empire. The results show that the collapse of Singasari was caused by a failure in security risk management due to overambitious foreign expansion (strategic overstretch), which triggered a military vacuum in the center of power. This moment of crisis was strategically managed by Raden Wijaya through pragmatic diplomacy and asymmetric military tactics to overthrow Jayakatwang by utilizing Mongol troops. The reconstruction of legitimacy was carried out through the reunification of the Wangsa Rajasa mandala through political marriages and the strengthening of historiographical narratives. This study concludes that Majapahit was not merely a successor to Singasari, but a refined form of the "Cakrawala Mandala Nusantara" vision that integrated inland agrarian strength with the global maritime economy. This geopolitical transformation positioned Majapahit as a thalassocratic empire capable of balancing domestic stability with regional influence on the international stage.